Pr3+-doped selenide-based chalcogenide glass mid-infrared fibre amplifier - Shen, Meili (2019)
Mid-infrared (MIR) fibre lasers beyond 4.0 μm with high brightness, high efficiency and good beam quality are in great demand in the fields of biomedical sensing, environmental monitoring and medical diagnostics. Since intense 3.5 - 6.5 μm MIR photoluminescence is shown in Pr3+-doped selenide chalcogenide glass fibre, it is believed that this fibre has potential to be employed as an active fibre for a MIR fibre laser or amplifier. As no laser threshold and fewer MIR optical components are required in an amplifier configuration, the Pr3+-doped selenide chalcogenide glass MIR fibre amplifier is explored in this Project. However, the challenges originating from the high fibre loss and complicated energy levels of Pr3+ ions, hinder the developing a MIR Pr3+-doped fibre amplifier. Hence, this Project is aiming to find an optimum optical design for a Pr3+-doped selenide chalcogenide glass fibre amplifier, which is able to achieve MIR signal amplification beyond 4.0 μm wavelength. The Pr3+-doped Ge-As-Se-Ga fibre was characterised in optical behaviour of the photoluminescence (PL) and PL lifetime (LT), using pump wavelengths at 1.55, 1.94 and 4.15 μm, respectively. PL results showed that different energy transitions are excited using the different pumping wavelengths. Both NIR (near-infrared) PL around 2.5 μm and MIR PL of 3.5 - 6.5μm were observed in Pr3+-doped Ge-As-Se-Ga fibre under each pumping at 1.55, 1.94 and 4.15 μm wavelength, respectively. Whereas, an energy transfer up-conversion at around 2.5 μm and the additional two NIR PL emissions at wavelengths of 1.05 and 1.41 μm, respectively, were found in the fibre using the 1.55 μm pumping. These latter are considered to be disadvantageous for a MIR fibre amplifier. It is suggested that the Pr3+-doped Ge-As-Se-Ga fibre amplifier is more appropriately pumped at 1.94 or 4.15 μm. In addition, the LTs of the 3H5 and (3F2, 3H6) levels of Pr3+ ions were evaluated to be 7.4 ± 0.03 ms and 1.9 ± 0.05 ms using a new method of 4.15 μm resonant pumping proposed in this Project. In particular, the LT of the (3F2, 3H6) level, for the first time, was successfully measured in the 4.15 μm resonantly pumped Pr3+-doped Ge-As-Se-Ga fibre. The 1.94 μm pumped cascaded Pr3+-doped MIR fibre amplifier was then numerically and experimentally investigated. The numerical investigation demonstrated that the pump power at 1.94 μm would be largely transferred to the NIR ASE power around 2.5 μm, rather than to the MIR signal amplification. A tiny signal amplification at 4.5 μm was predicted only in the case of the 1.94 μm co-pumped Pr3+-doped fibre amplifier with length of 0.8 m. Nevertheless, a 1.94 μm co-pumped Pr3+-doped Ge-As-Se-Ga fibre amplifier with 4.15 μm signal laser was experimentally designed, but no signal amplifier at 4.15 μm was observed in the fibre amplifier. These results reveal that a 1.94 μm pumped Pr3+-doped fibre amplifier is impractical for the MIR signal amplification beyond 4.0 μm. To explore further the Pr3+-doped selenide chalcogenide glass MIR fibre amplifier, a 4.15 μm resonantly pumped Pr3+-doped fibre amplifier was studied, which is beneficial from a lowered quantum defect performed in the resonant pumping. The simulation model with the pump excited-state absorption (ESA) and full spectral amplified spontaneous emission (ASE) of 2.0 - 6.0 μm was proposed for this fibre amplifier. The modelling results showed that a 4.15 μm counter-pumping fibre amplifier could achieve a power conversion efficiency (PCE) of over 62.8 % for signal wavelengths ranging from 4.5 to 5.3 μm. This is, to our best knowledge, the highest simulated PCE for a Pr3+-doped chalcogenide glass fibre amplifier yet reported. Furthermore, a maximum gain of 4.6 dB at a signal wavelength of 5.28 μm was experimentally demonstrated in a 4.15 resonantly pumped Pr3+-doped Ge-As-Se-Ga fibre amplifier with a broadband signal OPO (optical parametric oscillator) laser centred on 5.5 μm, as well as a new signal ESA at signal wavelengths around 5.5 μm. However, the signal ESA spoiled any further signal amplification particularly at wavelengths of 5.37, 5.51 and 5.57 μm, which should be suppressed in a resonantly pumped Pr3+-doped fibre amplifier. This work, to our best knowledge, is the first experimental demonstration of gain at MIR wavelengths in a Pr3+-doped chalcogenide glass fibre. Overall, during this Project, significant progress has been made on Pr3+-doped selenide chalcogenide glass MIR fibre amplifiers, and encouragingly a MIR signal amplification beyond 4.0 μm has been initially realised using a 4.15 μm resonantly pumped Pr3+-doped Ge-As-Se-Ga fibre amplifier.